Pharmacokinetics of Diclofenac after Oral Administration of its Potassium Salt in Sachet and Tablet Formulations - Marzo, Antonio; Bo, Lorenzo Dal; Verga, Filippo; Monti, Nunzia Ceppi; Abbondati, Guido; Tettamanti, Rosella Aleotti; Crivelli, Fabrizio; Uhr, Mario Richard; Ismaili, Shevqet (Arzneimittelforschung, 2000)
This paper reports the results of a pharmacokinetic study involving 24 healthy volunteers and designed to characterise the rate and extent of diclofenac absorption after the administration of a single dose of diclofenac (CAS 15307-86-5) potassium salt 50 mg in sachet (Voltfast®) and tablet (Cataflam®) formulations.Timed plasma concentrations of diclofenac during a 12-h-period after dosing were measured by means of HPLC with UV detection at 275 nm and a quantification limit of 10 ng/ml; the method was fully validated for pharmacokinetic purposes. These plasma concentrations were used to calculate Cmax, tmax, trapezoidal AUC0–t and AUC0–∞ and t1/2 by means of non-compartmental analysis. Cmax and tmax are the parameters expressing the rate of absorption, wehreas the AUCs reflect the extent of absorption. The rate of absorption with the sachets proved to be very fast, reaching peak values at 10 min in seven subjects and at 15 min in the remaining subjects: mean time was 13.68 min, with concentrations at 5 min being 38% of Cmax. The average time to peak concentration with the tablets was 53.10 min. The extent of absorption of the sachets and tablets was similar, with AUC0–∞ values of respectively 1362 and 1214 ng • ml−1 • h, and a 90% confidence interval 1.05–1.20.The highly soluble potassium salt of diclofenac was rapidly absorbed, especially in its sachet formulation, and thus appears to be an invaluable analgesic agent that is particularly useful for quick pain relief.
Keywords: CAS 15307-86-5; Cataflam®; Diclofenac potassium salt, absorption rate, bioavailability; plasma concentrations, sachet formulation; Voltfast®